PENGUATAN GENDER DALAM PENDIDIKAN ISLAM - Abdul Gani Jamora Nasution (Studi Multidisipliner: Jurnal Kajian Keislaman, 2017)
Gender is understood as a social relation that is attached to the public as sex. This sometimes makes the dilemma of social conservatives-textual, understand that women simply put "under the armpits of men" and not a few is found arbitrariness of male to female with jargon "as one likes me". To accommodate this, the Islamic Education plays an important role as understanding the gender acceleration. Given the spirit of Islamic education is to humanize human beings without distinction of sex.